Synthesis of β-Trifluoromethylthio- and β-Trifluoromethylseleno-α,β-unsaturated Ketones through Copper-Mediated Trifluoromethylthio(seleno)lation - Hou, Chuanqi; Lin, Xiaoxi; Huang, Yangjie; Chen, Zhirong; Weng, Zhiqiang (Synthesis, 2015)
An efficient and convenient synthetic methodology has been developed with which to construct β-trifluoromethylthio- and seleno-α,β-unsaturated ketones through copper-mediated trifluoromethylthio(seleno)lation of β-bromo α,β-unsaturated ketones. The corresponding ketone products were isolated in moderate to good yields and were efficiently converted into valuable alcohols.
Keywords: fluorine; trifluoromethylthiolation; selenium; enones; copper